2019
DOI: 10.1177/0310057x19886868
|View full text |Cite
|
Sign up to set email alerts
|

Transtracheal flow-regulated oxygen insufflation—a simple and safe method for prolonging safe apnoea time in difficult airway management: A report of two cases

Abstract: In the absence of upper airway patency, supraglottic methods of oxygen delivery become ineffective. We present two semi-elective difficult airway cases where oxygenation via the supraglottic route was deemed impractical due to upper airway obstruction. In order to facilitate safe airway management, apnoeic oxygenation was delivered via a narrow bore transtracheal cannula using a flow-regulated oxygen insufflator. The potential for safely prolonging apnoea time with this technique in both elective and emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Wexler et al [ 19 ], in a patient with a large base of tongue cancer causing near-complete airway occlusion, applied transtracheal oxygenation using a Rapid-O2 as a bridge to safe transtracheal jet ventilation. As jet ventilation could not be performed on an adult male patient with near-complete airway obstruction due to a large base of tongue cancer, Wexler et al [ 19 ] attempted to remove the mass to some extent while supplying oxygen through Rapid-O2 before creating enough space for applying jet ventilation. In the awake state, a 6-Fr (= ID 2 mm) Cook Transtracheal catheter (Cook Medical) was inserted through the cricothyroid membrane.…”
Section: Rapid-o2 Oxygen Insufflation Device (Rapid-o2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wexler et al [ 19 ], in a patient with a large base of tongue cancer causing near-complete airway occlusion, applied transtracheal oxygenation using a Rapid-O2 as a bridge to safe transtracheal jet ventilation. As jet ventilation could not be performed on an adult male patient with near-complete airway obstruction due to a large base of tongue cancer, Wexler et al [ 19 ] attempted to remove the mass to some extent while supplying oxygen through Rapid-O2 before creating enough space for applying jet ventilation. In the awake state, a 6-Fr (= ID 2 mm) Cook Transtracheal catheter (Cook Medical) was inserted through the cricothyroid membrane.…”
Section: Rapid-o2 Oxygen Insufflation Device (Rapid-o2)mentioning
confidence: 99%
“…Given that the minute volume is 5–8 L/min, hypercarbia cannot be avoidable. However, instead of waiting for SaO 2 to drop by 93% in Wexler et al’s case [ 19 ] in which it took 6–8 min to drop to 93%, if we adjust inspiration and expiration time in a ratio of 2:10 as described above, hypercarbia may occur in a less severe form. However, it is difficult to maintain this ratio in reality.…”
Section: Rapid-o2 Oxygen Insufflation Device (Rapid-o2)mentioning
confidence: 99%
“…The Rapid-O2™ oxygen insu ation device (Rapid-O2 ® ) is a rescue oxygenation device for use in "cannot intubate, cannot oxygenate" (CICO) events, which consists of a T-connector with an extension tubing attached to a catheter with a Luer lock connector 1,2 . Data from Heard's animal wet lab studies 3 demonstrated that, by extrapolation to humans, 1,000 mL of oxygen was needed for the initial rescue of an adult which equates to 4 s of insu ation at oxygen ow rate of 15 L/min.…”
Section: Introductionmentioning
confidence: 99%
“…An additional 500 mL of oxygen was adequate once the arterial oxygen saturation (SaO 2 ) decreased to 93% after the initial oxygen supply. Percutaneously, a 14 G catheter was used 2,4 . On the basis of this strategy, Wexler et al 2 applied transtracheal oxygenation using Rapid-O2 as a bridge to safe transtracheal jet ventilation in a patient with a large tongue base cancer causing near-total airway occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…There is a scientific body of evidence that hypoxemia can be prevented by deep insufflation of oxygen in the laryngeal space and trachea during apneic episodes [9][10][11][12]. Mitterlechner et al reported that oxygen saturation in a test-lung of a manikin remains significantly higher when using a specific laryngoscope blade designed for laryngeal oxygen insufflation, compared to nasal oxygen insufflation [9].…”
Section: Introductionmentioning
confidence: 99%